Arabs and Ideology in the Region of Comparative Literature Subject Study: Critique and Analysis of Ahmad Abdol Aziz’s Book - Hadi Nazari Monazam (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Comparative literature does not have the same and specific meaning. Actually, as a result of extensive alteration of meanings (eloquence) and development in the region of research, it can be said that nowadays just the mentality of accosting by literature and different cultures are dominant. Arab’s researchers are increasing and their approaches are varied. As a matter of fact, they are interested in searching a specific identity for Arab’s comparative literature, an identity that does not have any dependence on west and its matters. However, talking about Arab’s comparative literature is still new. This paper makes an attempt to study Ahmad Abdolaziz’s book entitled Nahva Nazariyya Jadida Leladab Almogharan by using descriptive and analytical and comparative ways; it also aims to review the positive points, difficulties, and content issues. This book is published in two copies and the author invited the readers to a new comparative literature bravely. But, the result shows that his attempt is an approach between France classicism and American unbridle and free ideology.He refers to France theory in the comparative part, and it is not an exaggeration if he said we cannot find anyspecific book’s idea in the world of comparative literature as well as Arab comparative literature.